The impact of coach gender on team performance: A quantitative analysis of women's five-a-side basketball leagues - Kulaijiang, Palizha (Universitas Tanjungpura, 2025)
Background and Study Aim. As women's participation in professional sports continues to grow, the presence and impact of female coaches have attracted increasing scholarly attention. Despite this, empirical evidence regarding the effect of coach gender on team performance remains inconclusive. This study aims to examine the causal impact of head coach gender on team performance in women